2020
DOI: 10.1002/aoc.5756
|View full text |Cite
|
Sign up to set email alerts
|

Coordination chemistry of H‐spirophosphorane ligands towards pentacarbonylchlororhenium(I) – synthesis, structure and catalytic activity of complexes

Abstract: Synthesis of a group of carbonyl rhenium coordination compounds with hydrospirophosphorane ligands was carried out and described. Different symmetrical HP(OCH2CH2NH)2L1, HP(OCH2CMe2NH)2L2, HP(OC6H4NH)2L3, and unsymmetrical ligands HP (OCMe2CMe2O)(OC6H4NH) L4 were found to coordinate to the rhenium center as bidentate P,N donor ligands yielding fac‐[ReCl (CO)3Ln], where n = 1–4. Furthermore, monodentate coordination was also observed in some cases, as was clearly presented in the case of [ReCl(CO)2(L4‐κ2P,N)(L4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Organophosphorus compounds occupy an important place in many materials sciences and biologically active substances for medical and agricultural use, such as agrochemicals, pharmaceuticals and natural products [1–3] . Moreover, they are widely employed as versatile chemical reagents or as ligands for transition metal in organic synthesis [4–9] . Among the various synthetic approaches to organophosphorus compounds, the direct construction of phosphorus‐carbon (P−C) bond is of particular importance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Organophosphorus compounds occupy an important place in many materials sciences and biologically active substances for medical and agricultural use, such as agrochemicals, pharmaceuticals and natural products [1–3] . Moreover, they are widely employed as versatile chemical reagents or as ligands for transition metal in organic synthesis [4–9] . Among the various synthetic approaches to organophosphorus compounds, the direct construction of phosphorus‐carbon (P−C) bond is of particular importance.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrospirophosphorane (HSP) is an important kind of the pentacoordinated phosphorus compounds containing a P−H bond, which may be used as a hydrophosphorylation reagent. In recent years, HSPs are also found to be a new type of potential ligand to catalyze organic reactions [8] . Furthermore, our group found that pentacoordinate spirophosphorane was a type of potential organocatalyst to catalyze organic reactions [25] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 9 ] While low‐valent rhenium(I) complex [ReCl(CO) 3 {P(OCH 2 CMe 2 NH)OCH 2 CMe 2 NH 2 }] was successfully utilized in dimerization reaction of substituted enynes. [ 10 ] Moreover, we have previously reported on rhodium(I) hydrospirophosphorane effective catalysts for the isomerisation of 1‐hexene. In the presence of modified ligand P (OPh) 3 , rhodium complexes have been shown to catalyze regioselectively hydroformylation of 1‐hexene.…”
Section: Introductionmentioning
confidence: 99%